Relationship between 3D and 2D global longitudinal strain in patients with acute myocardial infarction after percutaneous revascularization. (4th February 2022) - Tomoaia, R; Beyer, RS; Zdrenghea, D; Dadarlat-Pop, A; Cismaru, G; Gusetu, G; Chetan, IMI; Minciuna, IA; Simu, GR; Hada, N; Ganea, A; Pop, D
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): This research was funded by "Iuliu Haţieganu" University of Medicine and Pharmacy, Dept. of Cardiology, Cluj-Napoca, Romania. This paper was published under the frame of European Social Found, Human Capital Operational Programme 2014-2020, project no. POCU/380/6/13/125171 Introduction: Impaired longitudinal strain (GLS) is associated with increased wall stress following acute myocardial infarction (MI). However, little is known about the relationship between three-dimensional (3D)-GLS and two-dimensional (2D)-GLS. The aim of this study was to evaluate the relationship between 3D-GLS and 2D-GLS and also the association of 3D-GLS with specific biomarkers (NT-proBNP and Troponin) in patients with acute MI following percutaneous revascularization (PCI).  Methods: We included 100 patients with acute MI after successful PCI with a left ventricular ejection fraction (LVEF) >40%. 2D-GLS and 3D-GLS were assessed using speckle-tracking echocardiography and plasma concentrations of NT-proBNP and high sensitive troponin were analyzed.  Results: The patients had a mean age of 67.1 ± 13.1 years. 69 patients were diagnosed with ST-elevation MI (STEMI). Mean 3D-GLS was of -9.44 ± 4.35% and mean 2D-GLSwas of -10.1 ± 3.9%. 3D-GLS showed a strong correlation with 2D-GLS (r=-0.57, p < 0.001) and LVEF (r=-0.58, p < 0.001), a moderate correlation with NT-proBNP (r = 0.22), but no correlation with Troponin (r = 0.19). There was no difference (paired t-test) between 3D-GLS and 2D-GLS (p = 0.56, mean of differences of 0.65), but the limits of agreement were wide (-6.8% and  8.11%). Conclusion: 3D-GLS showed small bias compared to 2D-GLS, but wide limits of agreement. The correlation between 3D-GLS and NT-proBNP was only moderate in acute MI. 3D-GLS might offer additional advantages in patients with complex geometry after acute MI due to faster data acquisition and lack of geometric assumption, but future studies are needed to confirm its role.